X^2+kx+25=0

Simple and best practice solution for X^2+kx+25=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X^2+kx+25=0 equation:


Simplifying
X2 + kx + 25 = 0

Reorder the terms:
25 + X2 + kx = 0

Solving
25 + X2 + kx = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-25' to each side of the equation.
25 + X2 + -25 + kx = 0 + -25

Reorder the terms:
25 + -25 + X2 + kx = 0 + -25

Combine like terms: 25 + -25 = 0
0 + X2 + kx = 0 + -25
X2 + kx = 0 + -25

Combine like terms: 0 + -25 = -25
X2 + kx = -25

Add '-1kx' to each side of the equation.
X2 + kx + -1kx = -25 + -1kx

Combine like terms: kx + -1kx = 0
X2 + 0 = -25 + -1kx
X2 = -25 + -1kx

Simplifying
X2 = -25 + -1kx

Reorder the terms:
25 + X2 + kx = -25 + -1kx + 25 + kx

Reorder the terms:
25 + X2 + kx = -25 + 25 + -1kx + kx

Combine like terms: -25 + 25 = 0
25 + X2 + kx = 0 + -1kx + kx
25 + X2 + kx = -1kx + kx

Combine like terms: -1kx + kx = 0
25 + X2 + kx = 0

The solution to this equation could not be determined.

See similar equations:

| 26x^2-5x=0 | | x^2-8x-68=0 | | 25x^2+10x+1=9 | | -3+4x=-47 | | -4x+6=-166 | | 3(2+x)=x+18 | | 4x^2+4x+1=49 | | -3x-9=-3 | | 3p^2-12p+2=0 | | -6x+12=3(4x-8) | | 6x(3+2)=12-6x | | -19=x-8 | | 3x+4-4x=2(3x-5) | | x^2-10*x=119 | | 3x+7=22 | | 3x+4-4+2=(3x-5) | | -0.3x=12 | | 6x-12=2x | | 0.4x=10 | | 7n-63=35 | | 7-63=35 | | 5+6x=60+x | | 4x+24=11x-60 | | 7x-1=3x+9 | | 9x-15=5x+1 | | 4x^2-29x+41=-5x+6 | | 2n-14=16 | | y=5+4x^2 | | 9p+2t-2p+3t= | | 6x^2+41x-56=0 | | -5+7y=43-y | | 4x^2+29x+45=0 |

Equations solver categories